Pendampingan Peserta Kompetisi Sains Madrasah Bidang IPA Terpadu di MTsN 3 Aceh Barat - Widarta, Fajar (Universitas Negeri Semarang, 2025)
The mentoring activity for participants in the madrasah science competition (KSM) in the field of integrated science was held at MTsN 3 West Aceh, Aceh Province, in June 2024. The aim of this service activity is to provide learning assistance to KSM participants, strengthen students' understanding of the material to be tested, and provide tips and tricks in answering the tests. This service activity has three stages, namely the preparation stage, the implementation stage, and the evaluation stage. After participating in this mentoring activity, the students became more prepared to face the competition, as can be seen from the results of the evaluation that had been carried out.